Protecting the unprotected: mixed-method research on drug use, sex work and rights in Pakistan's fight against HIV/AIDS. (23rd March 2009) - Mayhew, S; Collumbien, M; Qureshi, A; Platt, L; Rafiq, N; Faisel, A; Lalji, N; Hawkes, S
Abstract : Objectives: To investigate the nature and extent of human rights abuses against three vulnerable groups (injecting drug users (IDUs) and male and female sex workers), to understand the social and sexual linkages between them and to examine how protecting their rights could enhance the impact of HIV prevention policies. Methods: In-depth interviews were carried out with 38 high-risk respondents (IDUs and female, male and transgender sex workers) and a bio-behavioural survey was performed of 813 IDU/sex worker respondents in Rawalpindi. Results: People in all vulnerable groups interacted both sexually and socially. All groups experienced human rights abuses by state and non-state actors which increased their HIV risk. Non-state actors, including relations and sex worker clients, are responsible for verbal, physical and sexual violence. State actors (particularly police) perpetrate harassment, exploitation and abuse of all vulnerable groups with impunity. Health service providers fail to provide adequate services for vulnerable groups. Conclusions: High levels of discrimination and abuse of human dignity of all groups studied were revealed. This violates their physical and mental integrity and also leads to an increased risk of HIV. The sexual and social interactions between groups mean that human rights abuses experienced by one high-risk group can increase the risk of HIV both for them and other groups. The protection of human rights needs to become an integral part of a multisector response to the risk of HIV/AIDS by state and non-state agencies. The Government of Pakistan should work at both legal and programme levels to protect the rights of, and minimise discrimination against, groups vulnerable to HIV in order to reduce the potential for the spread of HIV before the epidemic takes hold.